A smart algorithm for fault detection and location in electric power distribution system - Hamid Touijer; Mohammed El Alami; Mustapha Zahri; Mohamed Habibi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In an electric power distribution system (EPDS), fault location accuracy is critical for system stability. In the past, several algorithms have shown that they are inefficient. However, the results of these algorithms have been shown to be inefficient, and they should not be used for every sort of the faults. This paper presents a new algorithm capable to determine the location of fault accurately with low error rate. It is based on the voltage and current calculation at the source station for different types of faults by using either one power supply or double power supply. The work includes the formulation analytical development as simulation test results. The test results are produced by numerical simulation using data from a recognized distribution line in the literature.